Interplay Between Concerns-Based Adoption Model (CBAM) and Technological Pedagogical Content Knowledge (TPACK) as Employed by High School Teachers - Laurio, April (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the interplay between the Concerns-Based Adoption Model (CBAM) and Technological Pedagogical Content Knowledge (TPACK) as employed by high school teachers in the Basic Education Department of Tomas Claudio Colleges, Morong, Rizal. Specifically, it investigated how teachers’ personal and social concerns influence their level of technology integration in classroom instruction. A descriptive-correlational research design was utilized, employing a researcher-made questionnaire checklist to gather data from 75 high school teachers through total enumeration sampling. Statistical tools such as weighted mean, frequency distribution, F-test, and Pearson’s correlation coefficient were used to analyze the data.Findings revealed that the majority of respondents were female, aged 21–30 years, married, with MA units, and holding Teacher II and Teacher III positions. Most had 5–9 years of teaching experience and had participated in school-based in-service trainings on technology integration. Teachers demonstrated high levels of pedagogical knowledge and pedagogical content knowledge, while technological knowledge was comparatively lower. Social concerns showed a strong and significant relationship with all domains of TPACK, whereas personal concerns were significantly related only to foundational domains. Certain demographic variables, such as sex and educational attainment, significantly influenced selected TPACK domains.The study concluded that while teachers possess strong foundational competencies, social engagement plays a crucial role in enhancing effective technology integration. It is recommended that institutions implement structured and continuous professional development programs anchored on CBAM and TPACK frameworks. These programs should emphasize collaborative and socially oriented strategies, as well as targeted interventions tailored to teachers’ profiles. Future research may consider additional variables to further explore technology integration practices
Keywords: CBAM, TPACK, technology integration, high school teachers, descriptive-correlational, professional development